БЎЛАЖАК ПСИХОЛОГЛАРНИНГ КАСБИЙ РИВОЖЛАНИШИДА МОТИВАЦИОН СОҲАНИ ТАДҚИҚ ЭТИШНИНГ НАЗАРИЙ АСОСЛАРИ - Бабаниязова, М.Ю. (SCIENCE and SOCIETY, 2018)
Theoretical foundations in exploring motivational sphere for the professional development of future psychologists are analyzed in this article.